A sky beyond the storm - Tahir, Sabaa (Tahir, Sabaa. Ember in the ashes novel., 2020)
"Laia, Elias, and Helene must risk everything to defeat their foes--both human and supernatural--and prevent the coming of an otherworldly maelstrom"--